Spontaneous pneumomediastinum in an adolescent with diabetic ketoacidosis - Sánchez-Morillos, Daniel (2023)
A 15-year-old adolescent with no significant medical history admitted to the emergency room due to polydipsia, abdominal pain,nausea, vomiting, sudden dyspnea, and chest pain; On admission he was diagnosed with diabetic ketoacidosis in addition tospontaneous penumomediastinum by tomography. It is emphasized that pneumomediastinum associated with ketoacidosis is a rarecomplication but with a favorable evolution in most cases.